The Philippines Indigenous Peoples Rights Act and ILO Convention 169 on tribal and indigenous peoples: exploring synergies for rights realisation. Issue 2 (7th February 2020) - Doyle, Cathal
ABSTRACT: This article compares the Philippines' Constitutional and legislative recognition of indigenous peoples' rights with the provisions of ILO Convention 169 (C169). It contextualises the Philippines' contemporary recognition of indigenous peoples' rights, including the requirement to obtain their Free Prior Informed Consent (FPIC), within the country's colonial and post-colonial legal frameworks and considers the challenges faced in implementing the 1997 Indigenous Peoples Rights Act (IPRA). It posits that ratification of C169 and engagement with the ILO Supervisory bodies could benefit the indigenous peoples of the Philippines, given the ILO's extensive experience in overseeing the implementation of C169's provisions on good faith consultations in the Latin American context. It argues the ILO's tendency to occasionally resort to a binary veto-no-veto conception of FPIC disconnects the requirement for FPIC from the rights which it serves to safeguard. It suggests that ratification of C169 by the Philippines could assist the ILO Supervisory bodies to move beyond this conception of FPIC as a veto power. This broader rights-based conception of FPIC, as emerges from the IPRA, would be grounded on its historical underpinning, indigenous peoples' customary laws, and its importance for the realisation of their self-determination and territorial rights as recognised under contemporary international law.